Recombinant frizzled1 protein attenuated cardiac hypertrophy after myocardial infarction via the canonical Wnt signaling pathway - Fan, Jingjing; Hagenmüller, Marco; Riffel, Johannes; Meyer, Sören; Zhang, Min; Hardt, Stefan (OncoTarget, 2018)
Postinfarct cardiac hypertrophy is an independent risk factor for heart failure and sudden death. Regression of cardiac hypertrophy has emerged as a promising strategy in the treatment of myocardial infarction (MI).Here we hypothesized that frizzled1 (FZD1), a receptor of the canonical Wnt signaling pathway, is a novel mediator of ischemia-associated cardiac hypertrophy. MI was induced in mice by left anterior descending(LAD) coronary occlusion. One week after MI, the expression of FZD1 was found to be notably increased in the left ventricles (LVs) of the MI-mice compared to shams. Mouse recombinant FZD1 protein (RFP) was subcutaneously injected in the mice to provoke autoimmunization response. Anti-FZD1 antibody titer was significantly increased in the plasma of RFP-treated mice. RFP significantly mitigated the MI-induced cardiac hypertrophy and improved cardiac function in the MI mouse hearts. Moreover, increased heart and LV weights, myocardial size and the expression of β-myosin heavy chain in the MI-mice were also found to be attenuated by RFP. FZD1 was found to be significantly up-regulated in hypoxia-treated neonatal rat cardiomyocytes (NRCMs). Silencing FZD1 by siRNA transfection notably repressed the hypoxia-induced myocardial hypertrophy in NRCMs. Mechanistically, activation of canonical Wnt signaling induced by MI, e.g., β-catenin and glycogen synthase kinase-3β, was restrained in the LVs of the MI-mice treated by RFP, these inhibition on canonical Wnt signaling was further confirmed in hypoxic NRCMs transfected with FZD1 siRNA. In conclusion, immunization of RFP attenuated cardiac hypertrophy and improved cardiac function in the MI mice via blocking the canonical Wnt signaling pathway.
Published: December 12, 2017
Der Name des Verfassers Sören Meyer ist in der Autorenliste falsch geschrieben
Gesehen am 21.04.2020